2014
DOI: 10.3944/aott.2014.2981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aircast brace and elastic bandage on physical performance of athletes after ankle injuries

Abstract: Although external supports restrict the foot-ankle range of motion in specific ratios, these restrictions did not adversely affect the athlete's physical fitness. The Aircast® orthosis was more effective than the elastic bandage in reducing injury risk, preventing repetitive injuries and providing an early return to sports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…Results similar to those of Günay et al 26 were found by Boyce et al 16 in an attempt to determine the functional outcome of the ankle of nonathletes after a moderate or severe inversion injury. They compared the effects of a standard treatment with Aircast ankle brace against ENAB application in a randomized controlled trial of high methodological quality (7/10 PEDro).…”
Section: Effects Of Enab In Functional Outcome After Musculoskeletal supporting
confidence: 76%
See 4 more Smart Citations
“…Results similar to those of Günay et al 26 were found by Boyce et al 16 in an attempt to determine the functional outcome of the ankle of nonathletes after a moderate or severe inversion injury. They compared the effects of a standard treatment with Aircast ankle brace against ENAB application in a randomized controlled trial of high methodological quality (7/10 PEDro).…”
Section: Effects Of Enab In Functional Outcome After Musculoskeletal supporting
confidence: 76%
“…18,[24][25][26][27][28][29][30][31][32][33][34] A summary of included studies is presented in Table 1. The studies in this review included both athletes 26,34 and nonathletes.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 3 more Smart Citations